The Bible in the early Irish church: A.D. 550 to 850 - McNamara, Martin (Commentaria Ser., 2022)
Intro -- ‎Contents -- ‎Preface -- ‎Acknowledgements -- ‎Abbreviations -- ‎Introduction -- ‎Chapter 1. Irish Scholars: Early Medieval Ireland &amp -- Continental Europe -- ‎Chapter 2. Irish Biblical Texts, Glossarial Material, and Commentaries -- ‎Chapter 3. Bible Influences: Early Irish Latin &amp -- Vernacular Literature -- ‎Chapter 4. Christological and Historical Interpretation in the Psalms -- ‎Chapter 5. Cathach of St Columba &amp -- the St Columba Series Psalm Headings -- ‎Chapter 6. Apponius' Commentary on the Canticle of Canticles -- ‎Chapter 7. Josephus Scottus' Abbreviatio commentarii Hieronymi in Isaiam -- ‎Chapter 8. Theodulf of Orléans' Bible Commentary and Irish Connections -- ‎Chapter 9. Background to Irish Gospel Texts -- ‎Chapter 10. Glossed Text on Matthew's Gospel -- ‎Chapter 11. The Irish Origin of Vienna 940: A Commentary on Matthew -- ‎Chapter 12. Hiberno-Latin Apocalypse Commentaries: Purpose and Theology -- ‎Conclusion -- ‎Appendix 1. Updates to Bernhard Bischoff's "Wendepunkte" List -- ‎Appendix 2. Libri scottice scripti in St Gallen Stiftsbibliothek Catalogue -- ‎Appendix 3. Critical Edition of Canticle Section of De enigmatibus -- ‎Appendix 4. Irish Gospel Texts Publication project -- ‎Bibliography -- ‎Index of Modern Authors -- ‎Index of Manuscripts -- ‎Index of Scriptures -- ‎Index of Writers and Writings -- ‎Index of Subjects, Persons and Places.